Analisis Faktor Inflasi Bulanan Provinsi Banten 2011-2017 [Factor Analysis of Monthly Inflation in Banten Province, 2011-2017] - Euis Naya Sari (Pusat Penelitian, Badan Keahlian DPR RI, 2019)
Understanding the changes of inflation rate in a specific region is very essential, in order for the local government to maintain the inflation and to issue policies when inflation instability occurs. Inflation rate is one of the important indicators that reflects the economic development of a region. Inflation rate is measured by involving several variables taken from various types of expenditures. This study therefore aims to analyze subgroup expenditure variables which play significant role in explaining the monthly inflation rate in Banten Province, by focusing on the Consumer Price Index of three major cities, i.e. Serang, Tangerang, and Cilegon, using literature studies supported by quantitative descriptive analysis Kaiser-Meyer-Olkin Test, Bartlett Test, and factor analysis. For the factor analysis, the monthly data series for the period of 2011-2017 (84 months) consisting of 35 subgroups of goods/services, each of which is formed by several commodities, is analyzed. The data is obtained from the prices of goods/services recorded in every week or month. The results showed that, based on the factor analysis, only 26 variables out of 35 subgroup variables can be grouped into 5 factors, the remaining subgroup variables cannot be included in any factor. These 26 variables can explain as much as 34 percent in the variation of the monthly inflation rate. Meanwhile, the other 66 percent is explained by other factors which are not included in the model. In addition, the study also concluded that the causes of inflation during the study period were demand-pull inflation and cost-push inflation.Keywords: consumer price index, inflation, Banten Province AbstrakPerkembangan tingkat perekonomian dipengaruhi oleh banyak faktor, salah satunya adalah inflasi. Sementara itu tingkat inflasi sendiri banyak dipengaruhi oleh beberapa variabel, seperti pengeluaran yang dikelompokkan menjadi berbagai subkelompok. Dengan demikian, pemahaman tentang perkembangan tingkat inflasi sangat penting untuk diketahui oleh pemerintah daerah agar dapat mempertahankan tingkat inflasi dan mengeluarkan kebijakan ketika terjadi masalah. Berkaitan dengan hal itu, penelitian ini bertujuan menganalisis variabel-variabel pengeluaran subkelompok yang berperan dalam menjelaskan tingkat inflasi bulanan di Provinsi Banten. Penelitian ini fokus pada data ekonomi Provinsi Banten tahun 2011-2017, terutama pada Indeks Harga Konsumen (IHK) dari tiga kota besar di Banten, yaitu Serang, Kota Tangerang, dan Kota Cilegon, dengan menggunakan kajian pustaka yang ditunjang dengan analisis deskriptif kuantitatif dan Uji KMO (Kaiser-Meyer-Olkin), Uji Bartlett, serta Analisis Faktor terhadap data sekunder. Dalam analisis faktor digunakan 5 faktor yang berasal dari data inflasi pada 35 subkelompok pengeluaran barang/jasa dengan data series bulanan tahun 2011-2017 (84 bulan). Masing-masing subkelompok terbentuk dari beberapa komoditas yang datanya berasal dari pencatatan harga barang/jasa di setiap minggu atau bulannya. Hasil kajian ini menunjukkan, berdasarkan hasil analisis faktor dari 35 variabel subkelompok yang dipilih, hanya 26 variabel yang dapat dikelompokkan ke dalam 5 faktor, sisanya tidak masuk dalam faktor manapun. Sebanyak 26 variabel tersebut dapat menjelaskan variasi tingkat inflasi bulanan di Provinsi Banten, yaitu sebesar 34 persen. Sisanya dijelaskan oleh faktor lain yang belum masuk di dalam model. Selain itu, dapat dijelaskan pula bahwa inflasi di Provinsi Banten selama periode penelitian disebabkan oleh demand-pull inflation dan cost-push inflation. Kata kunci: indeks harga konsumen, inflasi, Provinsi Banten